Pixel classification method in optical coherence tomography for tumor segmentation and its complementary usage with OCT microangiography. Issue 4 (18th December 2017) - Moiseev, Alexander; Snopova, Ludmila; Kuznetsov, Sergey; Buyanova, Natalia; Elagin, Vadim; Sirotkina, Marina; Kiseleva, Elena; Matveev, Lev; Zaitsev, Vladimir; Feldchtein, Felix; Zagaynova, Elena; Gelikonov, Valentin; et al.
Abstract : A novel machine‐learning method to distinguish between tumor and normal tissue in optical coherence tomography (OCT) has been developed. Pre‐clinical murine ear model implanted with mouse colon carcinoma CT‐26 was used. Structural‐image‐based feature sets were defined for each pixel and machine learning classifiers were trained using "ground truth" OCT images manually segmented by comparison with histology. The accuracy of the OCT tumor segmentation method was then quantified by comparing with fluorescence imaging of tumors expressing genetically encoded fluorescent protein KillerRed that clearly delineates tumor borders. Because the resultant 3D tumor/normal structural maps are inherently co‐registered with OCT derived maps of tissue microvasculature, the latter can be color coded as belonging to either tumor or normal tissue. Applications to radiomics‐based multimodal OCT analysis are envisioned. Abstract : En face projection of the mouse colon carcinoma CT‐26 tumor on mouse ear delineated with proposed algorithm. A novel machine‐learning framework to distinguish between tumor and normal tissue in optical coherence tomography (OCT) has been developed. Prospects of complementary usage of tissue classification and OCT angiography have been demonstrated and applications to radiomics‐based multimodal OCT analysis have been envisioned.